Authentication-chains: blockchain-inspired lightweight authentication protocol for IoT networks - Al Ahmed, Mahmoud Tayseer; Hashim, Fazirulhisyam; Hashim, Shaiful Jahari; Abdullah, Azizol (Multidisciplinary Digital Publishing Institute, 2023)
Internet of Things networks (IoT) are becoming very important in industrial, medical, and commercial applications. The security aspect of IoT networks is critical, especially the authentication of the devices in the network. The current security model in IoT networks uses centralized key exchange servers that present a security weak point. IoT networks need decentralized management for network security. Blockchain, with its decentralized model of authentication, can provide a solution for decentralized authentication in IoT networks. However, blockchain authentication models are known to be computationally demanding because they require complex mathematical calculations. In this paper, we present an Authentication-Chains protocol which is a lightweight decentralized protocol for IoT authentication based on blockchain distributed ledger. The proposed protocol arranges the nodes in clusters and creates an authentication blockchain for each cluster. These cluster chains are connected by another blockchain. A new consensus algorithm based on proof of identity authentication is adapted to the limited computational capabilities of IoT devices. The proposed protocol security performance is analyzed using cryptographic protocols verifier software and tested. Additionally, a test bed consisting of a Raspberry Pi network is presented to analyze the performance of the proposed protocol.